Resonant perovskite solar cells with extended band edge - Feng, Jiangang (2023)
Tuning the composition of perovskites to approach the ideal bandgap raises the single-junction Shockley-Queisser efficiency limit of solar cells. The rapid development of narrow-bandgap formamidinium lead triiodide-based perovskites has brought perovskite single-junction solar cell efficiencies up to 26.1%. However, such compositional engineering route has reached the limit of the Goldschmidt tolerance factor. Here, we experimentally demonstrate a resonant perovskite solar cell that produces giant light absorption at the perovskite band edge with tiny absorption coefficients. We design multiple guide-mode resonances by momentum matching of waveguided modes and free-space light via Brillouin-zone folding, thus achieving an 18-nm band edge extension and 1.5 mA/cm2 improvement of the current. The external quantum efficiency spectrum reaches a plateau of above 93% across the spectral range of ~500 to 800 nm. This resonant nanophotonics strategy translates to a maximum EQE-integrated current of 26.0 mA/cm2 which is comparable to that of the champion single-crystal perovskite solar cell with a thickness of ~20 μm. Our findings break the ray-optics limit and open a new door to improve the efficiency of single-junction perovskite solar cells further when compositional engineering or other carrier managements are close to their limits.